Cenário da assistência técnica e extensão rural no estado no estado do Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Technical assistance and rural extension (ATER) is the main tool for transferring knowledge and technology to rural producers. Brazil is a country whose main economic source is agriculture, but it still has difficulties in offering adequate technical assistance to farmers, mainly in family farming. The first step to improve this situation is to quantify and qualify ATER. Thus, the present work aims to evaluate, based on the 2017 Agricultural Census, the access and type of ATER offered to producers in the State of Pará. Producers were quantified in terms of access, the type of technical assistance received, credit lines, income obtained on the property and the group of agricultural activities they carry out. It was found that ATER in the State of Pará is still a reality restricted to 4% of the establishments visited. Rural producers who have access to the ATER service are categorized in higher income brackets than those who do not receive it. Producers who do not have access to ATER services are then involved in activities related to temporary crops, followed by livestock activity and permanent crops. While those who have access to ATER are mostly livestock farmers, followed by those who develop temporary and permanent crops. Most of the producers evaluated by the Census are family farmers and among these, the majority had access to PRONAF credit lines and a smaller proportion to PRONAMP.
Keywords: Extensão Rural; Agricultura Familiar; Desenvolvimento Rural; CNPQ:: CIÊNCIAS AGRÁRIAS